Algoritma C4.5 Pada Sistem Analisis Data Untuk Klasifikasi Nasabah Sebagai Dasar Promosi Penjualan Produk Asuransi - Sholihul Umam; Febrian Wahyu Christanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
PT. Sun Life Financial is a company engaged in the field of financial consulting or insurance services. This company processes customer classification data still using calculations manually and using Ms. Excel. The system development method in this research uses RAD (Rapid Application Development). The method for pro-cessing customer classification data uses the decision tree algorithm C4.5. The strengths of this algorithm in-clude the ability to process numerical and discrete data, are easily interpreted, and are fastest among other algorithms. That the results of the user satisfaction questionnaire stated 48% strongly agreed, 45% agreed, 5% were enough, and 2% stated disagreed. The conclusion was that the data mining information system applica-tion that was built successfully resolved the problem to help find the cause of the dead policy (Lapse) or active policy (Inforce) at PT. Sun Life Financial Indonesia.